2018
DOI: 10.1002/ajh.25307
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of myeloproliferative neoplasms in patients exposed to ionizing radiation following the Chernobyl nuclear accident

Abstract: Myeloproliferative neoplasms (MPNs) driver mutations are usually found in JAK2, MPL and CALR genes, however, 10–15% of cases are triple negative (TN). A previous study showed lower rate of JAK2 V617F in Primary Myelofibrosis (PMF) patients exposed to low doses of ionizing radiation (IR) from Chernobyl accident. To examine distinct driver mutations, we enrolled 281 Ukrainian IR-exposed and unexposed MPN patients. Genomic DNA was obtained from peripheral blood leukocytes. JAK2 V617F, MPL W515, type 1- and 2-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…The study found that ionizing radiation exposed MPN patients display a different genetic profile compared to unexposed patients where the incidence of JAK2 V617F mutation was significantly less in the radiation exposed patients. Other findings included a higher rate of type-1 like CALR mutations and triple negative MPN in the ionizing radiation exposed group versus unexposed patients [ 88 ]. A study by Mele et al, reported that living in tuff houses, a building material containing gamma-emitting radionuclides, increases the risk for ET [ 89 ].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…The study found that ionizing radiation exposed MPN patients display a different genetic profile compared to unexposed patients where the incidence of JAK2 V617F mutation was significantly less in the radiation exposed patients. Other findings included a higher rate of type-1 like CALR mutations and triple negative MPN in the ionizing radiation exposed group versus unexposed patients [ 88 ]. A study by Mele et al, reported that living in tuff houses, a building material containing gamma-emitting radionuclides, increases the risk for ET [ 89 ].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Thus, oncogenic microalterations can be studied, in particular, in MPN patients. This increases the search power for identification of potentially involved genes in MPN development (as 10-15% of MPN patients are negative for known mutations of the specific driver genes) [2,[5][6][7].…”
mentioning
confidence: 99%
“…However, it has been observed that patients who test positive for the JAK2 genetic mutation have a higher risk for developing MPNs [52,53]. A low dose of ionizing radiation has been associated with an increased risk of developing MPNs, due to somatic mutations in the JAK2 gene (JAK2 V617F variant) [54]. New data point out that there is an association between environmental exposure and somatic mutations in environment-sensitive genes, such as homozygosity of CYP1A1 rs4646903, CYP1A2, EPHX1 rs2234922, and Tp53 alleles [55].…”
Section: Pathological Hematopoiesismentioning
confidence: 99%